2019
DOI: 10.1111/mec.14988
|View full text |Cite
|
Sign up to set email alerts
|

The future of parentage analysis: From microsatellites to SNPs and beyond

Abstract: Parentage analysis is a cornerstone of molecular ecology that has delivered fundamental insights into behaviour, ecology and evolution. Microsatellite markers have long been the king of parentage, their hypervariable nature conferring sufficient power to correctly assign offspring to parents. However, microsatellite markers have seen a sharp decline in use with the rise of next‐generation sequencing technologies, especially in the study of population genetics and local adaptation. The time is ripe to review th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
136
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(142 citation statements)
references
References 186 publications
(195 reference statements)
5
136
0
1
Order By: Relevance
“…Our study was not directly designed for the comparison of the power of genome‐wide neutral SNPs and microsatellites on parentage and relatedness analyses. Recent studies aimed to do so have shown that even few hundreds of genome‐wide SNPs outperform microsatellites in parentage assignment accuracy and relatedness estimation (Flanagan & Jones, ; Thrasher, Butcher, Campagna, Webster, Lovette, ), including in very small populations (Andrews et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Our study was not directly designed for the comparison of the power of genome‐wide neutral SNPs and microsatellites on parentage and relatedness analyses. Recent studies aimed to do so have shown that even few hundreds of genome‐wide SNPs outperform microsatellites in parentage assignment accuracy and relatedness estimation (Flanagan & Jones, ; Thrasher, Butcher, Campagna, Webster, Lovette, ), including in very small populations (Andrews et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…With that said, there are relatively few studies to date that effectively combine existing pedigree data with genomic estimates of relatedness to inform pairing recommendations (but see Hogg et al, 2019;Ivy, Putnam, Navarro, Gurr, & Ryder, 2016). To date, these studies are largely limited to SNPs being used for parentage reconstruction (reviewed in Flanagan & Jones, 2019), where unknown or uncertain relationships are reconstructed using empirical data and software (e.g., Whalen, Gorjanc, & Hickey, 2019), and more complete pedigrees are used moving forward. Alternatively, there is an option to produce empirical estimates of relatedness for all founders or breeding individuals in conservation breeding programmes-as suggested in Ivy et al (2016) , this approach requires caution, as the calculation of pedigree-based identity by descent for subsequent generations-including kinship and gene diversity-will be affected by the addition of empirical data .…”
Section: Management Implicationsmentioning
confidence: 99%
“…Studies of multiple parentage were stimulated by the advent of molecular techniques, primarily analyses of microsatellite DNA but in the future perhaps single nucleotide polymorphisms (SNPs), that allowed assessment of paternity (reviewed by ref. []). Molecular studies document the proportion of litters or clutches with multiple paternity and the number of sires that contribute to each of the broods.…”
Section: Introductionmentioning
confidence: 99%